Quantum Field Theory Under the Influence of External Conditions (QFEXT09) 2010
DOI: 10.1142/9789814289931_0018
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Casimir Effect in Wedge Geometry and the Energy-Momentum Tensor in Media

Abstract: The wedge geometry closed by a circular-cylindrical arc is a nontrivial generalization of the cylinder, which may have various applications. If the radial boundaries are not perfect conductors, the angular eigenvalues are only implicitly determined. When the speed of light is the same on both sides of the wedge, the Casimir energy is finite, unlike the case of a perfect conductor, where there is a divergence associated with the corners where the radial planes meet the circular arc. We advance the study of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…A sketch of the setup is given in figure 1. The present work is closely related to our recent paper [1] in particular, and also to our earlier papers on the thermal Casimir effect [2][3][4][5][6].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…A sketch of the setup is given in figure 1. The present work is closely related to our recent paper [1] in particular, and also to our earlier papers on the thermal Casimir effect [2][3][4][5][6].…”
Section: Introductionsupporting
confidence: 59%
“…As mentioned, the only place where there is a need to use the Drude relation (3) explicitly is when m = 0. Actually, it is immaterial whether we use the experimental Lambrecht data (5) or the Drude relation directly.…”
Section: Numerical Calculationsmentioning
confidence: 99%
“…However, we [12] and others have shown that for real metals, where γ has a residual value at zero temperature, the free energy per area has a vanishing slope at the origin. Indeed, in the Drude model, the free energy per area has the behavior [13,14] …”
Section: Introductionmentioning
confidence: 99%
“…Step (i) was essentially achieved by Lifshitz in 1955 [7], and within the same theory, addressing step (ii) was apparently trivial. Surprisingly, up to now, the role of dissipation in the temperature correction to the force between two dissipative metallic slabs is unclear and at the center of hottest controversy around the Casimir effect [8][9][10][11][12][13][14][15]. Lifshitz adopts a 'matter' point of view to calculate the Casimir effect building on a stochastic (Langevin) version of the Maxwell equations where quantum fluctuating currents are responsible for the fields.…”
Section: Introductionmentioning
confidence: 99%